Portugal : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses that the average investment growth needed for Portugal was to achieve the 2-percent and 2.5-percent real GDP growth in the medium term. It is likely that the growth rate of investment must significantly exceed the projected 4.9 percent in order to achieve the GDP growth path envisaged in the 2017 Stability Program. Specifically, per staff estimates, investment needs to grow at around 8.5 percent per year in case the TFP growth remains at -0.26 percent. The challenges confronting Portuguese banks were discussed in the 2016 Article IV staff report, which highlighted low profitability and weak asset quality as key concerns. The regulatory environment has exerted positive pressure insofar as the review of business models has now become an integral part of the supervisory agenda, especially for Single Supervisory Mechanism (SSM)-supervised banks. Pursuant to the Capital Requirements Directive IV (CRD-IV), banks' business models are considered in the Supervisory Review and Evaluation Process (SREP) performed by the supervisory authorities not only to determine capital and liquidity requirements but also to assess banks' recovery plans.